Al2O3-MgO refractory castables with enhanced explosion resistance due to in situ formation of phases with lamellar structure. Issue 7 (May 2018) - dos Santos, T.; Pinola, F.G.; Luz, Ana P.; Pagliosa, C.; Pandolfelli, V.C.
Abstract: This work evaluated an alternative route (formic acid addition and in situ generation of hydrotalcite phases) to reduce the explosion trend of dense MgO-bonded refractory castables during their drying step. Aqueous suspensions containing different magnesia sources (caustic or dead-burnt) and hydratable alumina were firstly analyzed in order to identify the likelihood of generating these in situ compounds with a lamellar structure in mixtures prepared with and without formic acid (hydrating agent). After that, high-alumina vibratable castables containing MgO and this carboxylic acid were evaluated and the following experimental tests were carried out: thermogravimetry, mechanical strength evaluation, apparent porosity and hot elastic modulus measurements. According to the obtained results, the thermal decomposition of the formed hydrotalcite-like phases led to samples' mass loss over a broader temperature range, preventing their explosion even when a critical heating rate (20 °C min −1 ) was applied during the tests. Besides that, no deleterious effect to the refractories' mechanical properties were observed during firing (i.e. softening at high temperatures). Thus, the addition of formic acid and the in situ formation of hydrotalcite-like phases is suggested as an alternative route to the conventional incorporation of amorphous silica or polymeric fibers into the castable dry-mixes to prevent the explosion of MgO-bonded refractories.